Studi Kasus: Penerapan Stretching Static Untuk Menurunkan Intensitas Nyeri Pada Lansia Osteoarthritis - Feri, Jhon; Juartika, Wella; Nurlela, Nurlela (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Osteoarthritis is an inflammatory disease of the joints that causes pain and stiffness in the joints in older adults. Joint pain management in older adults can be treated with static leg stretching exercises. Leg stretching static exercise is a relaxation technique through static life activities and active life which is expected to reduce the intensity of pain and muscle stiffness through a training process that makes the muscles flexible and ready to move and helps the body transition from less movement to more activity, without causing tension. Research Objectives: To describe the nursing implementation of applying static stretching to reduce pain intensity in elderly osteoarthritis in the Citra Medika Public Health Center working areaLubuklinggau City in 2023. Research Method: Descriptive research, with a case study approach, through 2 subjects with a medical diagnosis of osteoarthritis, which shows the nursing problem of acute pain. This research was conducted by implementing leg static stretching exercises for 15-30 minutes for five visits. Numerical pain assessment is used to carry out pre-and post-implementation assessments. Research Results: Implementation was carried out for one week (06-12 April 2023) on subjects I and II. In both subjects, the intensity of pain before the action was in the moderate category (scale 7) for subject I, and in subject II, it was in the moderate category (scale 6). The result was that after the implementation of 5 visits, the results of the two subjects showed a decrease in pain intensity, becoming mild pain (pain scale 3). Conclusion: The application of static foot stretching as physica activity, education on diet managemen, as a companion to osteoarthritis drug therapy has tshows effective results in reducing the pain intensity of older adults with osteoarthritis